The water footprint of biodiesel produced from sunflower in South Africa - Netshifhefhe, Khwathiso; Jordaan, Henry (MDPI, 2022)
The use of feedstock crops for the production of biodiesel suggests that biodiesel production may have a major impact on the scarce freshwater resource in South Africa. This paper aimed to assess the green plus blue water footprints (WFgreen+blue) of biodiesel produced from sunflower in South Africa using the Global Water Footprint Standard approach. The green (WFgreen) and blue water footprint (WFblue) at the farm level were assessed for sunflower grown under the rain-fed and irrigation production system respectively. The results show that 2617 m3 and 2477 m3 are required to produce 1 ton of rain-fed and irrigated sunflower respectively. At the processing level, about 7.12 L of blue water is required to produce 1 L of biodiesel from sunflower. The WFblue at the processing stage of biodiesel produced from irrigated sunflower was 1.01 m3/GJ, compared to 1.15 m3 m3/GJ from rain-fed sunflower. The WFgreen+blue of biodiesel produced from irrigated and rainfed sunflower was 2477 and 2617 m3/ton, respectively. WFgreen was the largest, accounting for about 59% and 99% for biodiesel produced from irrigated and rain-fed sunflower, respectively. It was further found that water consumption at the farm level accounted for about 99% of the WFgreen+blue of biodiesel in both production systems. Management practices that improve water use efficiency at the farm level may help to lower the WFgreen+blue of biodiesel. Interestingly, the WFgreen+blue is lower for biodiesel produced from irrigated sunflower than for rainfed sunflower. The blue water scarcity assessment showed that blue water scarcity is low during the period when sunflower requires water. As such, purely from a water use perspective, irrigated sunflower production in the Orange Riet Irrigation Scheme may be considered sustainable.
Keywords: Water footprint; Biodiesel; Sunflower-biodiesel value chain; Production systems; Water sustainability; Water resources management; Policy and governance